Y - 3x = -8
y = 3x - 8...slope here is 3. A perpendicular line will have a negative reciprocal slope. All that means is " flip " the slope and change the sign. So the slope we need is -1/3.
y = mx + b
slope(m) = -1/3
(3,2)...x = 3 and y = 2
now we sub and find b, the y int
2 = -1/3(3) + b
2 = -1 + b
2 + 1 = b
3 = b
so ur perpendicular equation is : y = -1/3x + 3
Answer:
x = 3
y = 1
Step-by-step explanation:
9x - y = 26 ---------------(I)
9x + y = 28 ---------------(II)
9x - y = 26
9x = 26 + y
Substitute 9x = 26 + y in equation (II)
26 + y + y = 28 {add like terms}
26 + 2y = 28 {subtract 26 from both sides}
2y = 28 - 26
2y = 2 {divide both sides by 2}
y = 2/2
y = 1
Substitute y =1 in equation (I)
9x - 1 = 26
9x = 26 + 1
9x = 27
x = 27/9
x = 3
x = 3
y = 1
In order to find the vector that points from A to B we need to subtract each component of A from the corresponding component of B, according to the formula:
v(a→b)=(b1−a1,b2−a2)
In this case we have :
v(a→b)=(−5−(−8),3−(−1))
<span>v(a→b)=(3,4)
</span>To find the magnitude we use the formula:
||v|= √(v1^2)+(v1^2)
So:
||v|= √(32)+(42)
||v|= √9+16
||v|= <span>√</span>25
||v|= 5